Implementing machine learning techniques to forecast floods In Bangladesh based on historical data - Toufique, S.M; Bhuiyan, Sadiq Uddin; Lateef, Ahmed; Zaman, Arman; Islam, Jubaer Bin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.